Molecular dynamics simulation of seeded crystal growth in glass - Wei Sun; Volkmar Dierolf; Himanshu Jain (Journal of Non-Crystalline Solids: X, 2022)
The mechanism of non-congruent growth of a crystal from glass has been sought using molecular dynamics simulations. Specifically, as a model of this process, the growth of a lithium niobate (LiNbO3) crystal seed sandwiched between two lithium niobosilicate (LNS) glass slabs has been simulated as a function of time and temperature. The growth of pre-existing crystal is strongly affected by the orientation of crystal seed, temperature, and the SiO2 concentration in the surrounding LNS glass matrix. The orientation of LiNbO3 seed surface that has inherently larger interplanar distance results in a relatively slower crystal growth. The addition of SiO2 to LNS system significantly decreases the crystal growth, which primarily occurs in the region devoid of Si. The suppressive effect of SiO2 on growth rate can be traced to the existence of defect complex comprising of Si substituted at the Nb site and a nearby Nb vacancy.